2012
DOI: 10.1016/j.econedurev.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Back to school: An application of human capital theory for mature workers

Abstract: Publication informationEconomics of Education Review, 31 (1): 168-178 Publisher ElsevierItem record/more information http://hdl.handle.net/10197/4435 There is a vast literature on the decision to enroll in higher education, but it focuses almost entirely on traditional students: 18 year olds graduating from high school. Yet less than half of students at degree-granting institutions are in the traditional 18-22 age range; nearly 40 percent are at least 25. This paper examines the enrollment behavior of persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…As questões como competitividade e prestígio profissional e a possibilidade de estudar de forma continuada aparecem como elementos de destaque nos estudos sobre políticas organizacionais e capital humano (LEPAK; SNELL,1999;HOLTOM;MITCHELL;LEE, 2006;KESSLER;LULFESMANN, 2006;JEPSEN;MONTGOMERY, 2012;DA CUNHA et al, 2010).…”
Section: Políticas Organizacionais: Assistência E Benefícios Motivaçunclassified
“…As questões como competitividade e prestígio profissional e a possibilidade de estudar de forma continuada aparecem como elementos de destaque nos estudos sobre políticas organizacionais e capital humano (LEPAK; SNELL,1999;HOLTOM;MITCHELL;LEE, 2006;KESSLER;LULFESMANN, 2006;JEPSEN;MONTGOMERY, 2012;DA CUNHA et al, 2010).…”
Section: Políticas Organizacionais: Assistência E Benefícios Motivaçunclassified
“… 3. Studies have indicated little practical difference between logit, probit, and linear regressions when the same dichotomous outcome variables were analyzed (Dey & Astin, 1993; Jepsen & Montgomery, 2012; Shuster, 2012). Since linear regression is easier to interpret (Angrist & Pischke, 2009), it was used to analyze the data for the current study. …”
mentioning
confidence: 99%
“…Other things being equal, individuals in less favorable occupations should generally have greater incentives to pursue additional education to improve their labor market position. Consistent with this argument, research shows lower wages (Jepsen and Montgomery 2012; Stenberg 2011) and (previous) unemployment (Hällsten 2011; Stenberg 2011) “push” individuals toward adult education. Both upgrading and sidestepping may facilitate exit from disadvantaged labor market positions, but upgrading would seem to offer better prospects for doing so; hence, it should appeal particularly to people in disadvantageous labor market positions.…”
Section: Theory and Hypothesesmentioning
confidence: 80%